Treatment approaches for idiopathic retroperitoneal fibrosis: a systematic review with meta-analysis - Annik Steimer; Mike O. Becker (BMC Rheumatology)
Abstract Background Currently, there is no standard therapy for idiopathic retroperitoneal fibrosis, so a systematic review was undertaken to assess the effectiveness of different treatment approaches. Methods A comprehensive search of English and German literature from 1980 to 2021 was conducted using PubMed, Embase, and PreMedline. To be included, studies must have had a minimum of two patients employing the same treatment approach and reporting relevant treatment outcomes. A meta-analysis with a subgroup analysis was conducted for the primary outcomes “regression of fibrosis,” “freedom from ureteric stents” and “relapse rate,” and the secondary outcome “clinical improvement.” The lack of homogeneous data prevented a subgroup analysis for the primary outcome “improvement in renal function.” Results The search resulted in a total of 3818 articles, of which 108 were selected for qualitative analysis involving a total of 1408 patients. For the meta-analysis 83 studies were included involving 1044 patients. The summary effect size of the outcomes “regression of fibrosis,” “freedom from ureteric stent” and “clinical improvement” was high with values between 80–97.9%. The summary relapse rate across studies was 18.1%. Subgroup analysis revealed no statistically significant differences in the effectiveness of treatment approaches for the outcomes “regression of fibrosis” (QM = 2.72, p = 0.74), “freedom from ureteric stent” (QM = 7.21, p = 0.13), “relapse rate” (QM = 11.34, p = 0.08) and “clinical improvement” (QM = 9.54, p = 0.15). Conclusions Considering the lack of clear evidence indicating that one drug is more effective than the other, the treatment choice should depend on factors such as the potential side effects of different drug therapies, patient comorbidities, and clinician expertise. The review protocol is registered on PROSPERO under the identification number CRD42019115744.